HMS Woodcraft Center and Iron Works a methods Study - Alipio, Ma. Theresa D.; Di, Nerissa C.; Lopez, Rassen M.; Ong, Jocelyn C.; Traya, Lloyd Apollo C. (Diliman, Quezon City College of Engineering, 1990)
This Methods Study was conducted on the manufacturing area of the HMS Woodcraft Center and Iron Works. The group confined its study to the manufacturing process itself, without regard to the delivery operations. The group didn't concern itself with iron work products anymore but rather concentrated on wood items namely doors, louvers and balusters. Being a job order type of manufacturing system, there are no definite sets of dimensions and designs of products for all these are dependent on customers' appeals. In the course of the plant visits made, the group was able to study and observe the management and the workers, the various processes and methods, the working conditions (i.e. lighting, physical environment) and the like. In the process of evaluating all the observations, the group found out that a lot of improvements can be made. However, they felt restricted in choosing their best recommendations because it involves quite radical changes. The management has earlier stated that such a change especially if it involves major renovations will not, in any way, be considered. The group, therefore, limited itself to improving the space utilization and ease of transportation and rearranging the various worktables and equipments. Various alternatives have been evaluated and through the procedure of listing the advantages and disadvantages of each alternative, the group came up with a standard criteria for choosing their optimal and feasible alternative. They firmly believe that upon the implementation of their recommendations, there will be a great improvement in the efficiency and productivity of the factory.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis